Digital Da'wah Communication in Marine Tourism: the Impact of Instagram Promotion on Millennial Muslim's Interest - Zulkarnain, Zulkarnain; Hendri, Ridar; Mujoko, Windasari Kamelia; Simanjuntak, Asnika Putri; Irsya, Habib (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Research on digital da'wah communication in marine tourism with the topic of analyzing the relationship between Instagram promotion and the interest of visiting millennial muslim’s to marine tourism faith-based destinations has been conducted in the marine tourism areas of Pandang Island and Salah Namo Island in Tanjung Tiram, Batubara Regency. This area is a coastal area of the East Coast of North Sumatra. Melalak Odan Instagram account is one of the many accounts that promote or preach tourist attractions in which it contains religious values, especially the tourist attractions of Pandang Island and Salah Namo Island, Batubara Regency, North Sumatra Province. This study aims to analyze the relationship between Melalak Odan's Instagram promotion and the visiting interest of millennial muslim’s to the tourist attractions of Pandang Island and Salah Namo Island, Batubara Regency, North Sumatra Province. This research uses a survey method with a quantitative approach. The results showed that the promotion carried out by Melalak Odan was in the very good category with a score of 8,838 and interest in visiting tourist attractions in the good category with a score of 3,258. The relationship between Instagram promotion and visiting interest is at the Spearman Rank correlation coefficient = 0.971**, meaning that the correlation coefficient value is in the category of a very strong relationship, with a sig value of 0.000 that Instagram promotion has a correlation with visiting interest, this is characterized by a sig value of 0.000 < smaller than α (0.05). With a positive form of relationship, Instagram promotion with visiting interest has a significant relationship.